2000
DOI: 10.1177/089124240001400403
|View full text |Cite
|
Sign up to set email alerts
|

State Science and Technology Planning in West Virginia: Challenges Facing Practitioners

Abstract: Many states that are involved in science and technology planning are selecting particular focus areas for state investment. In states with strong science and technology capacity, focus areas can relate to existing strengths. In predominantly rural states, there may not be a strong science and technology foundation, so new areas that do not reflect existing strengths may be selected. This article describes West Virginia’s first effort in statewide science and technology planning. The article shows that the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the envir-onmental perspective, firms may not urgently develop a specific technology unless the market and political prospects of the technology become clear. Some issues including user needs (Mackett and Edwards, 1998;Mohanty and Deshmukh, 1998;Lowe et al, 2000), stakeholders' opinion (Jiang and Klein, 1999), infrastructure (Calzonetti, 2000), supporting organization (Zysman et al, 2000), local economic development (Avineri et al, 2000), and local capital source (Lowe et al, 2000) were identified as the critical determinants influencing the decision-making of technology selection. Secondly, besides outside environmental factors, organizational characteristics play a major role in affecting the selection of a specific technology.…”
Section: Evaluation Criteria For Technology Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the envir-onmental perspective, firms may not urgently develop a specific technology unless the market and political prospects of the technology become clear. Some issues including user needs (Mackett and Edwards, 1998;Mohanty and Deshmukh, 1998;Lowe et al, 2000), stakeholders' opinion (Jiang and Klein, 1999), infrastructure (Calzonetti, 2000), supporting organization (Zysman et al, 2000), local economic development (Avineri et al, 2000), and local capital source (Lowe et al, 2000) were identified as the critical determinants influencing the decision-making of technology selection. Secondly, besides outside environmental factors, organizational characteristics play a major role in affecting the selection of a specific technology.…”
Section: Evaluation Criteria For Technology Selectionmentioning
confidence: 99%
“…According to previous studies (Calzonetti, 2000; Hsu et al, 2003; Barreto and Kypreos, 2004), evaluation criteria for technology selection can be divided into three main categories including environmental conditions, organizational characteristics, and technology attributes. In the environmental perspective, firms may not urgently develop a specific technology unless the market and political prospects of the technology become clear.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is all the more important as it is increasingly clear that livability concerns are especially of interest to new high tech firms engaged in the 'new economy'-as well as the broader service sector (Malecki 1991;Calzonetti and Gatrell 2000;Kotkin 2000). This is all the more important as it is increasingly clear that livability concerns are especially of interest to new high tech firms engaged in the 'new economy'-as well as the broader service sector (Malecki 1991;Calzonetti and Gatrell 2000;Kotkin 2000).…”
Section: Quality Of Lifementioning
confidence: 99%